Mortality Pattern of Nili-Ravi Buffaloes under Organised Herd in India - Das, Kalyan Sundar; Singh, Ghansham; Singh, Jitendra Kumar; Paul, Shyam Sundar (Journal of Buffalo Science, 2012)
The objective of the study was to find out the mortality pattern of Nili-Ravi buffaloes under organised herd in tropical climate. An investigation was carried out on post mortem findings of 318 Nili-Ravi buffaloes maintained at Central Institute for Research on Buffaloes, Regional Station-Bir Dosanjh, Nabha, Patiala, Punjab over a period of 16 years (1994-95 to 2009-10). Each year was divided into three seasons i.e. hot-dry (March-June), hot-humid (July-October) and cold (November to February). Sex of animals was divided into male and female group. The age of animals were grouped into eight categories viz. up-to 30 days (d), 31-60 d, 61-90 d, 91-180 d, 181-365 d, 366-1095 d, 1096-3650 d and more than 3651 d. The causes of mortality, based on post-mortem findings, were classified into twelve classes e.g. major respiratory diseases (MARD), minor respiratory diseases (MIRD), major digestive disorders (MADD), minor digestive disorders (MIDD), cardiovascular diseases (CVD), parasitic diseases (PAD), infectious diseases (ID), musculoskeletal diseases (MSD), urogenital/reproductive diseases (UGD/RD), neurological disorders (ND), nutritional/metabolic/production diseases (NMD) and miscellaneous disorders (MD). Majority of the buffaloes died in the months of July to October. About two third of the buffalo deaths occurred before one year of their age. MARD followed by MAAD and CVD were the predominant causes of buffalo death under organised herd. This information will be beneficial in reducing buffalo mortality through adopting proper herd health programme of organized buffalo herd.